Evaluation of Christian values and holistic child development: A case study of Benguet State University-Elementary Laboratory School in La Trinidad, Benguet, Phillipines - Li, Jia (Southeast Asia Early Childhood Journal, 2021)
The school, being the second home of pupils, is the second major force in the formation of the pupils’ moral structure. It should be the crucial partner of the home in tempering the character of the youth and children with unbending quality, especially in values formation. In this case, it is necessary to evaluate the current status of values teaching and its implication for child development. The study utilized the descriptive design, particularly survey method. This method was used to describe the Christian value formation and levels of child development of pupils. The samples used for the study consisted of a total of fifty (50) Grade VI pupils aged from 11 to 14 years old. Convenience sampling technique was used. A descriptive method was applied in depicting the implication of these values to the community development. The study was done at the Benguet State University Elementary Laboratory School and BSU Guidance Office in La Trinidad, Benguet, Philippines. In sum, mean value ratings on holistic child development domains have indicated that ratings among pupils on the five (5) holistic child development aspects ranged from 2.35 to 2.87 indicating that these domains are manifested by pupils in the school excellently, except for the cognitive which reaches a satisfactory 2.35. The overall rate is 2.77 at the excellent level. This can be attributed to the very strong directive of the school to develop its pupils holistically preparing them to embrace life with the essential level of skills needed to address the rudiments of the formative years and unto the next level of education for them. Christian values in terms of repentance, reconciliation, stewardship, faith, worship of God perseverance, hope, trustworthiness, and responsibility were highly manifested by the pupils of the BSU Elementary Laboratory School because values education was integrated in the school curriculum.